2018
DOI: 10.1002/nop2.158
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with self‐management among Vietnamese adults with type 2 diabetes

Abstract: AimThe study described diabetes self‐management (DSM), diabetes knowledge, family and friends’ support, healthcare providers’ support, belief in treatment effectiveness and diabetes management self‐efficacy, and explored DSM's associations among Vietnamese adults with type 2 diabetes mellitus (T2DM).DesignA cross‐sectional design was applied.MethodsThe study used self‐report questionnaires to collect data from 198 participants. Descriptive statistics and structural equation modelling (SEM) was used for data an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 42 publications
2
22
1
Order By: Relevance
“…Our finding that T2D management self-efficacy is strongly associated with glycemic control above and beyond diabetes knowledge and diabetes self-management is an important finding for a number of reasons. Current theory is that disease knowledge and management self-efficacy are both antecedents of disease self-management, and it is only through their impact on disease self-management that they can improve disease outcomes or clinical targets [ 46 , 47 ]. The results of the present study suggest that diabetes management self-efficacy is not only strongly associated with blood glucose control, but that this association remains even after adjusting for diabetes self-management.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that T2D management self-efficacy is strongly associated with glycemic control above and beyond diabetes knowledge and diabetes self-management is an important finding for a number of reasons. Current theory is that disease knowledge and management self-efficacy are both antecedents of disease self-management, and it is only through their impact on disease self-management that they can improve disease outcomes or clinical targets [ 46 , 47 ]. The results of the present study suggest that diabetes management self-efficacy is not only strongly associated with blood glucose control, but that this association remains even after adjusting for diabetes self-management.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study of Vietnamese adults with T2DM ( N = 198) conducted in South Vietnam reported the majority of participants could not answer 50% of the items about diabetes knowledge correctly. Furthermore, they had low diabetes management self-efficacy scores indicating that they would be unlikely to change DSM behaviors (Dao-Tran et al, 2018). Many Vietnamese adults living with T2DM receive informal education from family, friends, and others diagnosed with diabetes for knowledge and decision making around self-care.…”
Section: Resultsmentioning
confidence: 99%
“…Some participants believed that adhering to these elements would either reduce the severity of diabetes or cure it. Chu (2011) found that participants were resistant to managing T2DM with prescribed oral antihyperglycemic medications and expressed little knowledge about T2DM, commonly connecting it to "eating too much sugar." Many study participants believed that family history and excessive sugar intake predisposed them to T2DM, while the majority perceived that stress, worry, and sadness associated with immigrant life caused diabetes (Carolan-Olah et al, 2013;Mull et al, 2001;A.…”
Section: Diabetes Knowledge and Beliefsmentioning
confidence: 99%
“…Self-care behaviour is the activities undertaken by people to manage their disease [26]. A critical element of diabetes care, self-care or self-management behaviour plays a significant role in maintaining individuals' health and wellbeing [27]. According to the American Association of Diabetes Educators, there are seven self-care behaviours that predict good health outcomes.…”
Section: Introductionmentioning
confidence: 99%